Comunidade tradicional raizama em Jangada/MT : produzindo a existência associadamente por meio de enxadas, ralos, sucuris e torradeiras - Monlevade, Ana Paula Bistaffa de (2018)
The dissertation is the result of a scientific investigation carried out in the Traditional Community of Raizama, located in the city of Jangada, 110 km from Cuiabá/MT. This community is home to around 70 farming families and/or rural workers living and surviving from the harvest of fruits and vegetables, as well as subsistence livestock and the production of cassava flour cooperatively through the Raizama I Association of Rural Producers. One of the main characteristics of traditional communities such as Raizama is their mode of production, which is consistent with societies where labor has not yet become a commodity, where there is a greater connection with natural resources and where market dependence already exists, but is not absolute. These human beings develop a special way of being, living and ensuring their survival, based on characteristics such as equality, solidarity and living together, as well as sharing the same worldview of society. Thus, the joint production developed in the community represents the dynamics of the material and immaterial reality of the worker, that is, it is what allows us to understand the meanings that labor develops in people's lives, behaviors, interactions in the group, sociability processes and control mechanisms. From the theories of dialectical historical materialism, this dissertation’s general objective is to analyze the contradictions and mediations found by the workers of the Traditional Community of Raizama/MT, when organized to guarantee their existence from joint production. The specific objectives of this research are: a) To identify elements of the economy, culture and knowledge present in the organization of the cooperative life of Raizama workers; b) To present the peculiarities of the cooperative production that permeate historical spaces and times of Raizama and what this represents for the production of material and immaterial life in community; c) Discuss the limits of existence and resistance of the cooperative production in Raizama against the model of capitalist production. The research was carried out in collective spaces of labor and socialization in places such as the cassava flour mill and in the task forces performed by the community. Data collection took place through semi-structured interviews, conversation circles, photographic records, filming and field diary. It was possible to observe, through research, that there are many contradictions, challenges and also forms of resistance found in Raizama, because it was possible to identify a peculiar reality, with the cooperative production permeating space and time, throughout the historical events of the community, until a specific moment when the limitations of this existence faces the reality of capitalism. In that environment, the workers of Raizama struggle to exist and live collectively, with a solidarity and reciprocity that is intrinsic to all of them. Thus, their resistance presents itself in the way it resists, reproduces or transforms the activities that confront the logic of mercantile exchange. Even coexisting with the dominant system, Raizama still retains traces of an inherited culture that was transmitted, mainly by being recounted one generation to another. By virtue of accumulated experience, the community transmits their culture and knowledge, and assure that cooperative production remains present in the community.